2020
DOI: 10.1097/md.0000000000020123
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of frequent adult emergency department users

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 29 publications
3
11
1
Order By: Relevance
“…The outcome variable was the frequency of ED user visits before and during the COVID-19 pandemic. Frequent ED users were defined as those with four or more ED visits in a year, and occasional ED users were defined as those with one to three ED visits [ 2 , 10 , 21 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The outcome variable was the frequency of ED user visits before and during the COVID-19 pandemic. Frequent ED users were defined as those with four or more ED visits in a year, and occasional ED users were defined as those with one to three ED visits [ 2 , 10 , 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…Emergency department (ED) crowding is a burden on public health [ 1 , 2 ], so understanding the characteristics of frequent ED users is a key concern of healthcare systems and policy makers [ 3 , 4 ]. Taiwan’s implementation of National Health Insurance in 1994 enhanced public access to healthcare.…”
Section: Introductionmentioning
confidence: 99%
“…Those with previous ED visits and hospitalizations were at high risk of ED visit, hospitalization, and death independent of other sociodemographic, medical, and behavioral factors in our study. A previous study from a single center ED revealed that frequent ED users were more likely to be in poorer health, older, or have a chronic disease or a mental health disorder than occasional ED users [ 18 ]. Therefore, post-discharge care for ED attenders should be suggested to reduce frequent use of emergency care and to protect the capacity of the ED (i.e., paramedic-delivered care transitions intervention [ 52 , 53 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, study populations were relatively small, and generalizability to the entire Korean population was not possible. In addition, the availability of study data from medical records other than those related to the need for emergent care was limited as was individual health-related behavior data [ 8 , 13 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Portugal, patients that visited at least four times a year the ED represented, in 2015, 12% of the number of ED users, but 35.9% of the total ED episodes [5]. HU contributes to ED crowding [6,7,8,9], resulting in a reduction in quality of care, increased waiting times, and increased healthcare professionals' stress [2,10]. Regular admissions to the ED suggest that the ED is not an excellent place to treat these patients (for their clinical and social needs) [11,10,12,13].…”
Section: Introductionmentioning
confidence: 99%